Humoriste, journaliste et artiste engagé - Farida Souiah (L’Année du Maghreb)
This article sheds light on the plurality of caricatures which are a humorous, a journalistic and an artistic act. It also analyzes the commitment of those who draw political cartoons in a non-democratic context. First, this article explores the history of caricatures in Algeria in a direct link with the development of comics and press. It deals with the constraints that face caricaturists since the independence of Algeria until now. The second part of this article reveals the critical power of caricatures by studying a collection of political cartoons drawn by Hic and Dilem about harga (undocumented migration).